2021
DOI: 10.1155/2021/9925135
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices (KAP) of Human Populations towards Malaria Control in Four Ecoepidemiological Settings in Cameroon

Abstract: Malaria remains a major public health problem in Cameroon. Critical steps to improve disease control include assessing human population adherence to vector control interventions, especially in areas with different cultural backgrounds. The present study seeks to assess the knowledge, attitude, and practices (KAP) of populations towards malaria prevention in four ecoepidemiological settings in Cameroon. A cross-sectional malaria KAP survey was conducted from August to September 2019 in households of the localit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
4
17
1
Order By: Relevance
“…This could lead to poor knowledge score about malaria, which consecutively affects their action towards malaria prevention and control measures. Our findings are consistent with the studies conducted in Indonesia [ 49 ] and Cameroon [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…This could lead to poor knowledge score about malaria, which consecutively affects their action towards malaria prevention and control measures. Our findings are consistent with the studies conducted in Indonesia [ 49 ] and Cameroon [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…Specific knowledge involving mosquitoes, such as distance of adult flight and survival of eggs, may not be apparent to residents as this information is usually communicated only if residents specifically asked national public health officers on this. Studies have shown that residents equipped with sufficient mosquito knowledge was essential to effective and timely vector prevention and control programmes 41 43 . Dengue outreach could be modified to include mosquito facts, to promote awareness and adherence to proper mosquito preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed characteristic of each site is provided in Table 3 . Physical characteristics of sites with superscript ( a ) is published in Kala-Chouakeu et al [ 37 ].…”
Section: Methodsmentioning
confidence: 99%